PENGEMBANGAN MODUL STATISTIKA UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS - Lestari Hati Buulolo (Universitas Nias Raya, 2022)
Mathematics is a very important subject in education because mathematics can develop logical reasoning, understand concepts and provide skills to students. The lack of adequate learning resources makes mathematics lessons difficult for students and affects students' understanding of concepts. The purpose of this research is to develop a statistical module that is valid, practical, and effective and can improve the ability to understand mathematical concepts. This research uses Research and Development (R&D) research and development methods. The development model used is the 4-D model (Four D-Models), namely; Define, Design, Development, Dissemination. The results of the validation test were obtained from expert validators, namely material expert validators, design expert validators, and linguist validators with an average value of 84.29 with a valid category. The results of the practicality test were obtained from the results of the students' responses to the limited class trial of 91.12% with a high category and very practical criteria, the results of the student responses from field trials being 92.74% with a high category, and very practical criteria. The results of the effectiveness trial were obtained from the results of student learning tests after using the module. The increase in the ability to understand mathematical concepts was seen in the limited class trial, the pret-test with an average score of 38.18, for the post- test an average score of 83.18 with an N-gain score of 0.8 in the high category. The field trial obtained an average pret-test score of 31.66, for the post-test the average score was 76.38 with an N-gain score of 0.65 in the high category. So it can be concluded that this module has met the valid, practical and effective criteria to be used as teaching materials. The researcher hopes that this module can be used to improve the ability to understand mathematical concepts, especially in statistical material.